Pengaruh Pemberian Minyak Zaitun terhadap Kejadian Striae Gravidarum pada Ibu Hamil di BPS DA., Str. Keb Bumi Waras Bandar Lampung - Susilawati Susilawati; Julia Julia (Jurnal Kesehatan, 2017)
As a result of the many changes that mother was during pregnancy, commonly mothers feel anxious and depressed to face of such changes. In the USA in 2004, from 8000, there were 21.9% of pregnant women who suffer from anxiety. In Indonesia, there were pregnant women who experience anxiety, as many as 107,000 people (28.7%). The aim of research were to determine the effect of olive oil on the incidence of striae gravidarum in pregnant women in BPS DA. Str. Keb Bumi Waras Bandar Lampung, in 2016. Design of this research was survey method analytic experiment, pretest-posttest design with control group. The population in this study were all pregnant women with primigravidae, aged pregnancy 20-28 weeks. The sampling technique was accidental sampling. Analysis of the data were used bivariate analysis using independent t-test. The result showed that there were 30 respondents of pregnant women who have striaegravidarum in BPS DA, Str. Keb Bumi Waras Bandar Lampung,in 2016. There were 15 respondents who were not given olive oil, and 15 respondents who were given olive oil. Average values of striaegravidarum in pregnant women who were not given olive oil were 2.93±1,831, while the average value striaegravidarum in pregnant women who were given olive oil in a days were 3.13±1.642. The results of independent sample t test were obtained p-value=0.007 (p-value<α=0.05), it was no significant influence between given of olive oil to striaegravidarum in mothers pregnant in BPS DA., Str. Keb Bumi Waras, Bandar Lampung, in 2016.